THU0394 COMPARISON OF TREATMENT RETENTION OF SECUKINUMAB AND TNF-INHIBITORS IN PSORIATIC ARTHRITIS. OBSERVATIONAL DATA FROM A NORDIC COLLABORATION. (13th June 2020) - Lindström, U.; Glintborg, B.; DI Giuseppe, D.; Schjødt Jørgensen, T.; Gudbjornsson, B.; Grøn, K. L.; Aarrestad Provan, S.; Michelsen, B.; Hetland, M. L.; Wallman, J. K.; Nordström, D.; Trokovic, N.; et al.
Abstract : Background: A head-to-head trial (EXCEED) has indicated similar effectiveness of secukinumab (SEC) and the tumor necrosis factor inhibitor (TNFi) adalimumab (ADA) in psoriatic arthritis (PsA). In the clinical setting, treatment retention serves as a combined measure of overall effectiveness and tolerability. Objectives: To explore baseline patient characteristics, and compare treatment retention rates for SEC and each of etanercept (ETN), infliximab (IFX), golimumab (GOL), certolizimab (CZP) and ADA in PsA. Methods: Patients starting SEC or any TNFi in 2015-2018, in the 5 Nordic countries, were identified in clinical rheumatology registers. Data were pooled for analysis and stratified by 1 st, 2 nd and ≥3 rd line of treatment. One year treatment retention was compared by crude Kaplan-Meier curves and a proportional hazard model for risk of discontinuation, censored at 1 year and adjusted for sex, age, country and baseline CRP, patient global and use of csDMARD, with ADA as reference. Results: In total, 6062 patients with PsA were included, contributing 8172 treatment starts (table 1 ). SEC was mainly used as 2 nd or ≥3 rd line treatment. The survival curves and 1-year treatment retention rates, stratified by line of treatment, were similar for SEC compared to the TNFis, with some differences between the different TNFi (fig 1, table 2 ). Adjusted hazard ratios (HR) also indicated similar risk of SEC withdrawal compared to ADA (table 2 ). Conclusion: In this large study of bDMARD treatment of PsA in clinical practice, SEC was most often used as 2 nd or ≥3 rd line treatment, and the treatment retention of SEC was comparable with that of TNFi. Further analyses, taking into account other comorbidities, channeling and effectiveness will be presented. Acknowledgments: UL and BG are shared first, and LJ and LEK shared last authors. Partly funded by Nordforsk and FOREUM. Disclosure of Interests: Ulf Lindström: None declared, Bente Glintborg Grant/research support from: Grants from Pfizer, Biogen and Abbvie, Daniela Di Giuseppe: None declared, Tanja Schjødt Jørgensen Speakers bureau: Abbvie, Pfizer, Roche, Novartis, UCB, Biogen, and Eli Lilly, Björn Gudbjornsson Speakers bureau: Novartis and Amgen, Kathrine L. Grøn Grant/research support from: BMS, Sella Aarrestad Provan Consultant of: Novartis, Brigitte Michelsen: None declared, Merete L. Hetland Grant/research support from: BMS, MSD, AbbVie, Roche, Novartis, Biogen and Pfizer, Consultant of: Eli Lilly, Speakers bureau: Orion Pharma, Biogen, Pfizer, CellTrion, Merck and Samsung Bioepis, Johan K Wallman Consultant of: AbbVie, Celgene, Eli Lilly, Novartis and UCB Pharma, Dan Nordström Consultant of: Abbvie, Celgene, Lilly, Novartis, Pfizer, Roche and UCB., Speakers bureau: Abbvie, Celgene, Lilly, Novartis, Pfizer, Roche and UCB., Nina Trokovic: None declared, Thorvardur Love: None declared, Niels Steen Krogh: None declared, Johan Askling Grant/research support from: JA acts or has acted as PI for agreements between Karolinska Institutet and the following entities, mainly in the context of the ARTIS national safety monitoring programme of immunomodulators in rheumatology: Abbvie, BMS, Eli Lilly, Merck, MSD, Pfizer, Roche, Samsung Bioepis, Sanofi, and UCB Pharma, Lennart T.H. Jacobsson Consultant of: AbbVie, Eli Lilly, Janssen, Novartis and Pfizer, Lars Erik Kristensen Consultant of: UCB Pharma (Advisory Board), Sannofi (Advisory Board), Abbvie (Advisory Board), Biogen (Advisory Board), Speakers bureau: AbbVie, Amgen, Biogen, Bristol-Myers Squibb, Celgene, Eli Lilly, Gilead, Forward Pharma, Janssen Pharmaceuticals, MSD, Novartis, Pfizer, and UCB Pharma